Socio-cultural evolution of the urban environment as an object of sociological analysis - Lebedeva Еlena V. (Journal of the Belarusian State University. Sociology, 2022)
The current stage of development of the urban environment is characterised by an increase in the role of urban public space; activation of network interaction of citizens; strengthening the relationship between physical and digital in the urban environment. The criteria for the evolution of the socio-cultural environment of the city are the ratio of private and public in the urban environment; the ratio of vertical horizontal interaction of citizens, as well as the degree of adaptation of citizens to the technological transformation of the city.